(untitled) (Studia Prawnicze / The Legal Studies, 2013)
Inspiracją do zbadania charakteru sankcji, jakie prawodawcy innych krajów przewidzieli w odpowiedzi na naruszenie zakazu manipulacji instrumentami finansowymi, była, generalizując, negatywna ocena decyzji w tym przedmiocie podjętej przez polskiego prawodawcę, dokonana w monografi i „Kryminalizacja manipulacji instrumentami finansowymi”. W pracy tej zawarty był wprawdzie rozdział odnoszący się do regulacji prawnych obowiązujących w Wielkiej Brytanii, Niemczech oraz Stanach Zjednoczonych, czyli krajach posiadających wysoko rozwinięte rynki kapitałowe, jednak rozważania te służyły przede wszystkim pokazaniu różnych sposobów definiowania manipulacji. Natomiast dla oceny charakteru sankcji, która grozi sprawcy manipulacji, taka perspektywa była zbyt skromna. The purpose of this study is primarily to present regulations in the selected. EU countries regarding the sanctions to combat market manipulation. From the perspective it is possible to evaluate decision on the nature of the sanction made by the Polish legislator. The EU countries which regulations have been selected to examine were: Austria, Bulgaria, the Czech Republic, France, Germany, Lithuania, the United Kingdom and Slovenia. The analysis of the regulation enables to distinguish a group of countries which legislators have opted for one regime of liability for market manipulation – it was the regime of the administrative responsibility. The second group consists of countries which legislators have opted simultaneously for two regimes of the responsibility: the administrative and the criminal liability. Even in this group of countries the administrative sanctions constitute the main measures to combat market manipulation. Therefore the decision of the Polish legislator to criminalize the majority of the kinds of behavior which constitute market manipulation has to be assessed as very punitive. In contrast to the presented the EU countries regulations, in Poland the criminal sanction is the main measure to combat market manipulation.